Extreme precipitation events and their relationships with circulation types in Italy. (4th April 2021) - Iannuccilli, Maurizio; Bartolini, Giorgio; Betti, Giulio; Crisci, Alfonso; Grifoni, Daniele; Gozzini, Bernardo; Messeri, Alessandro; Morabito, Marco; Tei, Claudio; Torrigiani Malaspina, Tommaso; Vallorani, Roberto; Messeri, Gianni
Abstract: Extreme precipitation (EP) events are life‐threatening phenomena that are expected to continue to increase because of ongoing climate change. In the past decade, these events have been caused by important and well‐documented variations in large‐scale atmospheric circulation. Identifying the trends, dynamics, and related causes of EP could help in recognizing geographical areas that are at great risk and reducing their adverse impacts, particularly on a relatively small area such as the Italian peninsula. The relationships between large‐scale circulation types (CTs) and EP were investigated using a long time‐series (1979–2015) of meteorological data recorded by 46 weather stations in Italy. EP was defined as the number of days with accumulated precipitation above the 90th percentile (R90p). The seasonal trends of R90p were not homogeneous and showed significant increases primarily in winter and spring. Only a few CTs were significantly related to R90p, and this relationship was strongly dependent on latitude, orographic exposure, and season. Heterogeneous seasonal trends for daily CT occurrences were also observed. 'Cyclonic' CTs grouped together showed significant increasing trends in all seasons, whereas 'Anticyclonic' ones showed a generalized decreasing trend, explaining, only partially, the increase of R90p observed in some stations. Meanwhile, the R90p trends seem to be more influenced by the variations in the internal characteristics of CTs (i.e., the variation of some meteorological parameters that characterize them) observed over the past few decades than by changes in CT frequencies but still with high heterogeneity in Italy. The results of this and other similar studies can provide useful support for the implementation of mitigation and adaptation strategies to minimize the impacts of severe weather, particularly in complex areas such as the Mediterranean basin. Abstract : Identifying the trends, dynamics, and related causes of extreme precipitation could help in recognizing geographical areas that are at great risk over the Italian peninsula. Therefore, the relationships between large‐scale circulation types based on COST733 software (PCT09) and Extreme precipitation (R90p) were investigated. Although some atmospheric circulations may induce an increase of extreme precipitation events, the reflection of climate change had a higher impact on the variation of internal characteristics of some circulations. MSLP, mean sea‐level pressure centroid maps for the nine classes of PCT09 classification.